The most fulminant course of the Marburg variant of multiple sclerosis—autopsy findings. (April 2015) - Nunes, JC; Radbruch, H; Walz, R; Lin, K; Stenzel, W; Prokop, S; Koch, A; Heppner, FL
Multiple sclerosis (MS) is usually a chronic and disabling inflammatory disease. Marburg's type of MS is characterized by rapid progression and severe disease course that leads to death within one year after the onset of clinical signs. We describe a fulminant clinical presentation of this malignant subtype of MS and discuss the neuropathological hallmarks as well as differential diagnoses of other fulminant demyelinating diseases. To the best of our knowledge, this is the most fulminant course of this MS variant reported in the literature.